Modified harmony search algorithm for location-inventory-routing problem in supply chain network design with product returns - Misni, F.; Lee, L. S. (Institute for Mathematical Research, Universiti Putra Malaysia, 2021)
This paper presents a study on the integration of location-inventory-routing problem by considering the returned products of an economic production quantity model in supply chain network design. This model assumes that the returned products can be re-furbished and re-entered into the market to be re-sold. The problem aims to minimise the total cost of establishing the depots, the cost of setup the production and inventory holding, and the cost of delivery travelled by the vehicles. This problem is solved by a proposed Modified Harmony Search (MHS) algorithm with dynamic parameter setting and multi-local neighbourhood search techniques. Computational experiments on benchmark instances show that the proposed MHS outperformed a standard HS for all cases, as well as most of the approaches from the literature.